OPTIMIZING INTERNATIONAL TRANSPORT ROUTES: A CASE STUDY ON THE SILK ROAD (International Seven Journal of Multidisciplinary, 2022)
This article examines the optimization of international transport routes, focusing on the Silk Road Economic Belt (SREB) as a key case within the broader framework of China’s Belt and Road Initiative (BRI). It explores how strategic investments in infrastructure, the application of emerging technologies such as blockchain and artificial intelligence, and the harmonization of cross-border policies contribute to more efficient and cost-effective logistics operations. By transforming traditional transit corridors into dynamic, integrated logistics systems, the Silk Road has significantly improved trade flows between Asia and Europe. The study also considers the geopolitical and environmental dimensions of transport optimization, showing how diplomatic cooperation and sustainability practices enhance long-term performance. Drawing on recent academic research, the article demonstrates that transport route optimization is not only a matter of operational efficiency but also a driver of economic development, political stability, and environmental responsibility. The findings suggest that the Silk Road offers a replicable model for other transnational logistics corridors worldwide.